Ways to improve speech confidance - Mustafina, Anna Djalilevna; Sobirova, Firuza Urunbaevna (Science and Education, 2023)
This study was intended to examine different methods to promote self-assurance during the oration and find out which of them are more useful. The study also explores the role of various factors such as body language, tone of voice, eye contact, and presentation skills in enhancing speech confidence. The article includes various scientific studies by scientists that aims to help readers improve their confidence and other necessary skills for successful speech.